New methods of train traffic control - Aitkhozhina, Aiman; Orazalina, Aida; Baiguzhina, Gulsezim (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
This article is written about a new concept of train traffic control. A topic of significant relevance in the field of organisational and safety aspects of train traffic. The existing system of train traffic control is based on the principles of application of field devices railway automation, and depending on their state driver provides movement or stopping of the train. Also on the monitoring panels, which are located in the control center, describes the state of floor devices, by them train dispatcher keeps track only the approximate location of the train. ETCS is based on the idea of continuous monitoring of the transport process using a combination of various technical means, thereby achieving a safe reduction in the transit interval, which means an increase in throughput. The ETCS is based on determining the location of the train, calculating the distance between trains, controlling the maximum permissible speed on the section, calculating the braking curve (depending on the speed over the distance traveled), comparing route data with the technical characteristics of the train. The requirements for ETCS devices are strict parameters of the accuracy of the navigation system: the error in determining the location of the eurobalance should not exceed ± 1 m, and the error of the odometers should not exceed ± 5% of the distance traveled.